2019
DOI: 10.1590/0366-69132019653732521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal treatment on the catalytic activity of a Fe-rich bentonite for the photo-Fenton reaction

Abstract: The objective of this work was to evaluate the degradation of rhodamine B dye from aqueous solution by photo-Fenton reaction under visible irradiation using a Fe-rich bentonite as a catalyst. The material was thermally treated at a low temperature (200 °C) and characterized by XRD, N 2 adsorption-desorption isotherms, FTIR, SEM-EDS and XRF. Iron leaching in aqueous solution after the photo-Fenton reaction was evaluated by atomic absorption spectroscopy. The material exhibited a mesoporous structure, containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…3. 팽창 실험 장비 및 방법 , 2006;POSIVA, 2007;Egirani et al, 2018;Zimmermann et al, 2019). XRD 분석 결과 카올리나이트와 일라이트는 Muscovite와 Alpha-SiO 2 로 구성되어 있음을 확인하였다.…”
Section: 이론적 배경unclassified
“…3. 팽창 실험 장비 및 방법 , 2006;POSIVA, 2007;Egirani et al, 2018;Zimmermann et al, 2019). XRD 분석 결과 카올리나이트와 일라이트는 Muscovite와 Alpha-SiO 2 로 구성되어 있음을 확인하였다.…”
Section: 이론적 배경unclassified
“…Amongst them, iron minerals are relatively less priced and can be separated magnetically from the reaction medium [43]. Applications o f Fe-rich bentonite [44], fly ash-based catalysts [45], and molybdenum carbide doped with nanostructured nickel [46] have been reviewed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This clay can exhibit excellent properties, as large specific surface area, high cation exchange capacity (CEC) and low permeability, which gives it a wide application as adsorbents and catalysts (BELBACHIR and MAKHOUKHI, 2017;ZONG et al, 2015). The work of Zimmermann et al (2019) showed an increase of the specific surface area of these clays when subjected to thermal treatment at 200 °C. Morphological characteristics of the sample were examined using scanning electron microscopy (SEM; Jeol, JSM 6010LV).…”
Section: Introductionmentioning
confidence: 99%
“…The photodegradation was determined by Liquid Chromatography coupled to Mass Spectrometry (LC−MS) using an electrospray ionization mass spectrometer (Agilent Technologies − 6460 Triple Quadrupole LC/MS) in order to verify the fragmentation of dye molecules. The methodology of equipment operation and analytical conditions are described byZimmermann et al (2019).…”
mentioning
confidence: 99%